The Effect of Liquidity, Solvency, Activity, and Profitability on Stock Return - Bias Kamajaya; Eny Kusumawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Every investor wants a large return with the smallest risk. For this reason, investors are required to be able to predict whether their investment will make a profit or not. This study aims analyzed the effect of liquidity, solvency, activity, and profitability on stock returns. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Sampling using purposive sampling method with predetermined criteria. The final sample used in this study was 260 samples. This type of research is quantitative using secondary data obtained from the financial statements of manufacturing companies. The analytical method used is multiple linear regression. The results of this study indicate that liquidity, solvency, and activity have no effect on stock returns, meanwhile profitability has an effect on stock returns.